THE ROLE OF PARENTS AND EDUCATORS IN SHAPING THE ISLAMIC CHARACTER OF YOUNG CHILDREN: A REVIEW OF QURAN-BASED CURRICULUM - Hasnawati; Wahyu; Saragih, Ismawati (JURNAL KAJIAN ISLAM MODERN, 2025)
This study aims to analyze the role of parents and educators in the formation of Islamic character in early childhood by reviewing the implementation of the Al-Quran-based curriculum. The main focus of this study is to identify effective strategies that can be optimized in instilling Islamic values ​​in children from an early age, both in the family environment and in educational institutions. This study uses a qualitative method with a descriptive-analytical approach. Data were collected through literature studies, interviews with parents and educators, and observations of the implementation of Islamic character education in several Islamic-based early childhood education institutions. The results of the study indicate that parents have a major role in forming children’s Islamic character through role models, Islamic parenting patterns, effective communication, and the habituation of Islamic values ​​in everyday life. Meanwhile, educators play a role in integrating Islamic values ​​into the curriculum, creating an Islamic educational environment, and using learning methods based on Islamic values ​​that are in accordance with child development. Supporting factors in the formation of Islamic character include a religious family environment, a structured Islamic education curriculum, and a community that supports the development of Islamic values. However, this study also found several obstacles, such as lack of parental attention due to busyness, negative influence of media and socializing, and limited educators who understand the concept of Islamic education in depth. This study concludes that there is a need to increase awareness and involvement of parents in children’s education through strengthening the curriculum based on the Qur’an, as well as creating a conducive learning environment so that children can grow into individuals who have noble morals and are able to face the challenges of the times based on Islamic values